2006
DOI: 10.1242/jeb.02241
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-induced cardiac contractility requires exogenous glucose,glycolysis and the sarcoplasmic reticulum in rainbow trout

Abstract: SUMMARY Recent data from our laboratory suggest that sex steroids promote contractile function in cardiac muscle of rainbow trout (Oncorhynchus mykiss Walbaum), and there are sex differences in hormone signaling and cardiac function. The current study investigated whether steroid-induced inotropism in electrically paced (0.5 Hz, 14°C) ventricle strips at 90%Lmax (1) has a metabolic requirement for exogenous glucose and (2) is associated with enhanced intracellular Ca2+ storage and release from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 54 publications
4
13
1
Order By: Relevance
“…Ryanodine reduced twitch force development at the first stimulus after a prolonged rest period [post-rest potentiation (Bers, 1985)] and the force developed at 1.1Hz in the presence of adrenaline at 15°C and in the absence of adrenaline at 23°C -a temperature close to the upper thermal limits of this species . Overall, the current results for Aarhus rainbow trout confirm the importance of the SR as a source of activator Ca 2+ and, in contrast to a previous study (Farrar et al, 2006), do not support an essential role of exogenous glucose for Ca 2+ loading/release in the SR of female rainbow trout. Even under aerobic conditions, glycolysis appears to be crucial for normal EC coupling in the heart of rainbow trout (Gesser, 2002) and mammals (Kockskämper et al, 2005).…”
Section: +supporting
confidence: 68%
See 3 more Smart Citations
“…Ryanodine reduced twitch force development at the first stimulus after a prolonged rest period [post-rest potentiation (Bers, 1985)] and the force developed at 1.1Hz in the presence of adrenaline at 15°C and in the absence of adrenaline at 23°C -a temperature close to the upper thermal limits of this species . Overall, the current results for Aarhus rainbow trout confirm the importance of the SR as a source of activator Ca 2+ and, in contrast to a previous study (Farrar et al, 2006), do not support an essential role of exogenous glucose for Ca 2+ loading/release in the SR of female rainbow trout. Even under aerobic conditions, glycolysis appears to be crucial for normal EC coupling in the heart of rainbow trout (Gesser, 2002) and mammals (Kockskämper et al, 2005).…”
Section: +supporting
confidence: 68%
“…However, previous (Gesser et al, 1982;Farrar et al, 2006;Battiprolu et al, 2007) and current data demonstrate that positive inotropic effects of a maximally effective dose of adrenaline occur during oxygen deprivation and recovery after oxygen deprivation, and these effects are independent of the presence of exogenous glucose. An additional study using iodoacetate to block glycolysis showed that inotropic responses to adrenaline under aerobic conditions do not require an active glycolytic pathway (Farrar et al, 2006). Together, these results suggest that aerobic and anaerobic metabolic pathways are capable of supporting adrenaline-induced changes in mechanical performance of the rainbow trout heart without exogenous glucose.…”
Section: +contrasting
confidence: 44%
See 2 more Smart Citations
“…Female ventricle strips do not maintain contractile force or resting tension in vitro under aerobic conditions as well as male preparations, whereas male preparations do not preserve contractile function as well as female preparations after hypoxia and reoxygenation (7). Inhibition of the glycolytic pathway during aerobic incubations of rainbow trout ventricle strips results in incomplete relaxation, increased resting force, and decreases in twitch force (22,35). However, compared with the mammalian heart, little is known about the relationship between anaerobic and aerobic energy metabolism in fish hearts.…”
mentioning
confidence: 99%